Evaluación técnico-financiera para el cambio del sistema de levantamiento artificial actual por bombeo por cavidades progresivas con motor en fondo de imanes permanentes en tres pozos de un campo petrolero (2018)
The purpose of this project is based on a study at three levels of a field located in the Basin of the Eastern Plains, which are currently presented with Electrosumergible Pumping as an artificial lifting system, presenting faults or inadequacies due to a very low production, high energy consumption and the presence of heavy crude with API gravity between 12.7 ° and 13.8 °. In first measurement, the generalities of the Basin of the Eastern Plains and of the field were classified, it is explained like the theoretical frame of the principles of production, the principle of operation of the Pumping by Progressive Cavities, the equipment in the bottom and the surface of the Electrosumergible Pumping and Pumping by Progressive Cavities with Motor in Permanent Magnet Fund. Then, the operation of the PC-PUMP design software is detailed. Subsequently, a selection selection will be made to select the best candidates to study, each operating operation of the selected wells will be described and an analysis of faults or operational problems in each one will be made.